The Impact of Writer’s Block on Academic Writing Performance: A Study of English Education Students - Sania Amila; Hesti Wahyuni Anggraini (Universitas PGRI Sumatera Barat, 2025)
This study aims to investigate the impact of writer’s block on academic writing performance among English Education students at Sriwijaya University.Employing a mixed-methods approach with Sequential Explanatory design, the participants were 59 sixth-semester students enrolled in the Academic Writing course, selected purposively as they had prior experience with Paragraph Writing and Essay Writing. Quantitative data were collected using a writing test and writer’s block questionnaire (QIWB) by Mike Rose (1981), and analyzed using Spearman’s rho. The findings revealed a correlation coefficient (r) of -0.023 and a significance value (p) of 0.865, indicating a very weak negative correlation that is not statistically significant. This result suggests that writer’s block does not meaningfully affect student’s academic writing performance, implying that it may be a minor factor compared to other influences such as language proficiency, time management, and motivation. Qualitative data were collected through open-ended questionnaires administered to 9 participants, selected purposively based on their writing test results (3 high achievers, 3 average, and 3 low achievers). The results showed that students still experienced writer’s block due to psychological pressure, lack of ideas, and overthinking, but they could overcome these challenges through peer support and self-regulation strategies. The study concludes that while writer’s block is present among students, its impact on academic writing performance is minimal, highlighting the importance of addressing broader cognitive and affective factors in writing instruction.